Of courtiers & princes : stories of lower court clerks and their judges - Peppers, Todd C. (Constitutionalism and democracy., 2020)
"Like almost all studies that have appeared since scholars realized--about twenty years ago--that law clerks play important roles in judicial decision-making, those collections focused on the Supreme Court. Given the importance of the Court and of its clerkships as stepping stones to greater things, this is not surprising. But federal courts, and cases, are far more numerous. In this final volume of his trilogy focusing on clerks, Peppers shows that the distinctive doings of lower court clerks are at least as important, and interesting, as those of their Supreme Court counterparts. Ruth Bader Ginsberg, among others, contributes"--